The rise of the rustbelt - Cooke, Philip (Philip N.) (UCL Press, 1995)
The Rise of the Rustbelt demonstrates the value of interchange and comparison of ideas and policies for industrial regeneration between three major regions: the Great Lakes of North America, the Ruhrgebiet of North-Rhine-Westphalia, and the industrial belt of South Wales. The top priority of these areas is to conserve and retain their status as industrial powerhouses by attracting investment to compensate for their dramatic structural decline over the past twenty years and more. They have much to learn from one another. Encompassing environmental and sociocultural issues, as well as those of i.